Novas abordagens para aumentar a sobrevivência e eficiência de cepas de Bacillus solubilizadoras de fosfato - Velloso, Camila Cristina Vieira (Universidade Federal de São Carlos, 2024)
NEW APPROACHES TO INCREASE THE SURVIVAL AND EFFICIENCY OF PHOSPHATE- SOLUBILIZING BACILLUS STRAINS. In a context where global population growth and the exacerbated impacts of climate change pose critical challenges to food security and environmental sustainability, the adoption of sustainable agricultural practices emerges as an urgent necessity. In this scenario, species of the genus Bacillus, notable for their resilience and ability to promote plant growth through, for example, the solubilization of nutrients such as phosphorus, are explored as microbial inoculants, due to their potential to increase agricultural productivity. However, the variability of environmental conditions highlights challenges regarding the survival and efficiency of these inoculants, demanding strategic innovations. This research proposes an integrated methodology aiming to enhance the survival and efficacy of phosphorus-solubilizing Bacillus strains, thus establishing a sustainable and ecologically responsible alternative to conventional chemical fertilizers. This approach was outlined through three strategic axes: 1) optimizing cultivation conditions to increase the microorganisms' resistance to environmental stresses; 2) encapsulation in biopolymeric matrices to ensure controlled release and protection of the inoculants; 3) the application of Laboratory Adaptive Evolution (ALE) to select strains with improved salinity and drought resistance and growth-promoting capabilities. Adjustments in the cultivation process parameters, such as pH and temperature, along with production scale, resulted in a significant increase in the production of resistant microbial spores, reaching a concentration of 1.31·1012 CFU/mL in a bubble column bioreactor, with a sporulation efficiency of 100%, heat resistance of 78.4%, and an energy efficiency 4.83·1010 CFU/J. The encapsulation technique, employing starch-based biopolymeric matrices with additives like maltodextrin, cellulose, and bentonite, demonstrated protection of the inoculants against environmental stressors, such as UV and extreme temperatures. Different release profiles were observed among the modified films, with variations in initial and prolonged release rates, demonstrating the influence of material properties on the diffusion of microorganisms. While the addition of maltodextrin accelerated the release of microorganisms, cellulose and bentonite increased retention and allowed for gradual release. The application of ALE resulted in the development of Bacillus strains with greater tolerance to saline and water stress, capable of solubilizing phosphorus, producing exopolysaccharides, and forming biofilms. This research offers a significant contribution to the advancement of sustainable agricultural practices by improving the viability and functionality of microbial inoculants, representing an alternative in the face of contemporary challenges of food security and environmental sustainability.
New approaches to increase the survival and efficiency of phosphate-solubilizing Bacillus strains
Keywords: Engenharia de bioprocessos; Esporos de Bacillus resistentes ao calor; Eficiência de esporulação; Inoculante microbiano; Filmes à base de amido; Encapsulamento; Liberação controlada; Proteção contra estresses abióticos; Evolução adaptativa de laboratório; Agricultura sustentável; Bioprocess engineering; Bacillus spore heat-resistance; Sporulation efficiency; Microbial inoculant; Starch-based films; Encapsulation; Controlled-release; Protection against abiotic stresses; Adaptive laboratory evolution; Sustainable agriculture; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA